Dental size reduction in Indonesian Homo erectus: Implications for the PU-198 premolar and the appearance of Homo sapiens on Java. Issue 90 (January 2016) - Polanski, Joshua M.; Marsh, Hannah E.; Maddux, Scott D.
Abstract: The recent recovery of a hominin maxillary third premolar, PU-198, within the faunal collections from Punung Cave (East Java) has led to assertions that Homo sapiens appeared on Java between 143, 000 and 115, 000 years ago. The taxonomic assignment of PU-198 to H. sapiens was based predominantly on the small size of the specimen, following an analysis which found little to no overlap in premolar size between Homo erectus and terminal Pleistocene/Holocene H. sapiens . Here, we re-evaluate the use of size in the taxonomic assignment of PU-198 in light of 1) new buccolingual and mesiodistal measurements taken on the fossil, 2) comparisons to a larger sample of H. erectus and H. sapiens maxillary third premolars, and 3) evidence of a diachronic trend in post-canine dental size reduction among Javan H. erectus . Our results demonstrate PU-198 to be slightly larger than previously suggested, reveal substantial overlap in premolar size between H. erectus and H. sapiens, and indicate a statistically significant reduction in premolar size between early and late Javan H. erectus . Our findings cast doubt on the assignment of PU-198 to H. sapiens, and accordingly, question the appearance of H. sapiens on Java between 143, 000 and 115, 000 years ago.